Herbert Fröhlich: A Physicist Ahead of His Time - Hyland, G. J (Springer, 2016)
This biography provides a stimulating and coherent blend of scientific and personal narratives describing the many achievements of the theoretical physicist Herbert Fröhlich. For more than half a century, Fröhlich was an internationally renowned and much respected figure who exerted a decisive influence, often as a ‘man ahead of his time’, in fields as diverse as meson theory and biology. Although best known for his contributions to the theory of dielectrics and superconductivity, he worked in many other fields, his most important legacy being the pioneering introduction quantum field-theoretical methods into condensed matter physics in 1952, which revolutionised the subsequent development of the subject. Gerard Hyland has written an absorbing and informative account, in which Herbert Fröhlich’s magnetic personality shines through.